2003
DOI: 10.1161/01.atv.0000098645.38676.cc
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vessel Development

Abstract: Abstract-Development of the coronary vascular system is an interesting model in developmental biology with major implications for the clinical setting. Although coronary vessel development is a form of vasculogenesis followed by angiogenesis, this system uses several unique developmental processes not observed in the formation of other blood vessels. This review summarizes the literature that describes the development of the coronary system, highlighting the unique aspects of coronary vessel development. It sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 89 publications
(112 reference statements)
2
36
0
Order By: Relevance
“…Two orifices within the RAS had also been reported in the same setting (Saidi et al, 2002). The separate orifices for the TCA and the RCA had been explained by insufficient unification of these two vessels, during their growth towards the ascending aorta (Reese et al, 2002;Wada et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Two orifices within the RAS had also been reported in the same setting (Saidi et al, 2002). The separate orifices for the TCA and the RCA had been explained by insufficient unification of these two vessels, during their growth towards the ascending aorta (Reese et al, 2002;Wada et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Morphological events that are involved in formation of the coronary vascular system have been well described, especially in avian systems (chick and quail) (Morabito et al 2002, Reese et al 2002, Wada et al 2003. Before stage 14 in the chick (embryonic day 9.5 in the mouse), the heart consists of two layers, an outer myocardial layer and an inner endocardial layer.…”
Section: Development Of the Coronary Vasculaturementioning
confidence: 99%
“…Vascular channel formation leads to the development of a vascular plexus that covers the heart. At later stages in development, this vascular plexus undergoes remodeling, giving rise to the mature coronary vascular system (Morabito et al 2002,Reese et al 2002,Wada et al 2003.Initial studies in avian systems have demonstrated that the proepicardial organ and the epicardium are required for coronary development because removal of either structure severely perturbs coronary vessel formation (Gittenberger-de Groot et al 2000). More recently, genetic analysis in the mouse has confirmed this observation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, researchers believed that coronary arteries (CAs) budded from the aorta during development in humans and other mammals (Hutchins et al, 1988;Wada et al, 2003;Tomanek, 2005). However, this theory of proximal CA development is inadequate, as it does not explain the known possible congenital abnormalities of the CA (Bogers et al, 1988).…”
mentioning
confidence: 99%